2016
DOI: 10.12940/jfb.2016.20.4.36
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Appearance Management Behaviors on Career Decision Level in Female College Students

Abstract: The objective of this study was to examine the effects of appearance management behaviors on career decision level among female college students. Based on previous studies on appearance management behaviors and career decision level, the items for a questionnaire were developed. For the study, we conducted a questionnaire survey among 292 students from women's university in Seoul. Factor analysis, correlation analysis and multiple regression analysis were performed using SPSS statistics 23. Results of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Four English and nine Korean language studies underline social factors that may influence body image in South Korea (Elfving-Hwang, 2016; Kim, 2014a, 2014b, 2016; Kim & Chung, 2016; Kim & Hwang, 2008; Kim, Lee, & Koh, 2010; Lee & Koh, 2006; Lee & Ku, 2006; Park & Cho, 2014; Park & Chung, 2012; Ryu et al, 2003; Shin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Four English and nine Korean language studies underline social factors that may influence body image in South Korea (Elfving-Hwang, 2016; Kim, 2014a, 2014b, 2016; Kim & Chung, 2016; Kim & Hwang, 2008; Kim, Lee, & Koh, 2010; Lee & Koh, 2006; Lee & Ku, 2006; Park & Cho, 2014; Park & Chung, 2012; Ryu et al, 2003; Shin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Other sociocultural themes found to be relevant to body image in South Korea include those related to social achievement and one’s social group such as appearance evaluation apprehension, values of conformity, and filial piety (Elfving-Hwang, 2016; Jung & Hwang, 2016; Kim, 2014b, 2016; Lee & Ku, 2006; Park & Chung, 2012; Ryu et al, 2003; Shin et al, 2017). As Holliday and Elfving-Hwang (2012) suggested, body management allows one to more aptly succeed in work and marriage given that physiognomy is embraced in South Korea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As individuals move forward in their chosen majors and strive for competitive career-related experiences (e.g., jobs and internships) during college, college is a time period that helps facilitate FP goals of improving and establishing the self and family in society along with appearance management behaviors. Indeed, studies have found that South Korean college students engaging in appearance management methods such as plastic surgery feel more efficacious in their job searches and confident in their career field (Kim, 2016; Kim & Kim, 2017). Therefore, associations between body image, acceptance of plastic surgery, FNE, and FP may be more salient for South Korean college students in general but also differ in their prominence across students depending on what college they go to as unique characteristics of a particular college (e.g., level of prestige) can create different atmospheres of competition.…”
Section: Discussionmentioning
confidence: 99%
“…국내 코칭관련 연구동향을 살펴보면 기업 내 코칭리더십(coaching leadership)이나 코칭행동이 구성원의 직무만족이나 조직몰입 이직의 도 등과 같은 조직유효성 변수에 미치는 영향 연구를 통해 코칭리더십 이나 관리자의 코칭행동에 따라 조직유효성에 차이가 있음을 규명하 였고 [11], 조직유효성을 극대화하기 위해서는 구성원들의 역량개발에 중점을 둘 수 있는 코칭 행동유형을 고려할 필요가 있다고 주장하였 다 [12]. 최근에는 학습코칭이나 [13], 감정코칭 [14], 커리어(career) 코칭 프로그램 [15] 등 획일적인 코칭에서 벗어나 대상자의 특성을 고려하여 다양하게 활용된 맞춤형 코칭을 시행하고 있으며 코칭의 종류 또한 다 양해지고 있다. 국내의 간호사들을 대상으로 한 연구에서도 코칭은 간 호업무 성과 [5]와 직무몰입 [16] 및 감성지능 [17]에 긍정적인 영향을 미 치는 것으로 나타났다.…”
unclassified